2017
DOI: 10.1038/s41598-017-04103-y
|View full text |Cite
|
Sign up to set email alerts
|

Spatially Confined Spin Polarization and magnetic sublattice control in (La,Sr)MnO3−δ Thin Films by Oxygen Vacancy Ordering

Abstract: Perovskite oxides are known for their strong structure property coupling and functional properties such as ferromagntism, ferroelectricity and high temperature superconductivity. While the effect of ordered cation vacancies on functional properties have been much studied, the possibility of tuning the functionality through anion vacancy ordering has received much less attention. Oxygen vacancies in ferromagnetic La0.7Sr0.3MnO3−δ thin films have recently been shown to accumulate close to interfaces and form a b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 43 publications
1
9
0
Order By: Relevance
“…We find that the alternate stacking of octahedral and tetrahedral layers in the BM phase produces A-type antiferromagnetism under compressive perpendicular strain (Table S2, Supporting Information). This result agrees with a previous report on LSMO/ STO, [11] which also revealed that spins in the octahedral and tetrahedral layers order parallel and antiparallel, respectively. The calculated distributions of Mn magnetic moments shown in Figure S6, Supporting Information, displaying distinctive peaks at 3.70 μ B and 4.35 μ B , confirm the existence of two magnetic sub-lattices.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…We find that the alternate stacking of octahedral and tetrahedral layers in the BM phase produces A-type antiferromagnetism under compressive perpendicular strain (Table S2, Supporting Information). This result agrees with a previous report on LSMO/ STO, [11] which also revealed that spins in the octahedral and tetrahedral layers order parallel and antiparallel, respectively. The calculated distributions of Mn magnetic moments shown in Figure S6, Supporting Information, displaying distinctive peaks at 3.70 μ B and 4.35 μ B , confirm the existence of two magnetic sub-lattices.…”
Section: Resultssupporting
confidence: 93%
“…The physical properties of ABO 3 perovskites alter drastically with the BOB bond lengths and bond angles through a changing degree of overlap between the d orbitals of the B-site cations and the p orbitals of the oxygen anions. Distortions and rotations of oxygen octahedra, often designed by heteroepitaxial growth, [37,38] have been shown to change the electronic structure, to produce electronic and magnetic anisotropies, [11,[39][40][41] and to stabilize ferroelectricity. [42,43] In this work, we demonstrate how migration and reordering of oxygen vacancies during simultaneous voltage pulsing and local mechanical straining produces a complex pattern of distorted oxygen tetrahedra, pentahedra, and octahedra in an epitaxial LSMO film.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…17,26 The lattice distortion and symmetry breaking cause redistribution of the t 2g and e g orbital populations that facilitates the tunability of a wide range of physical properties. 17,23 The evolution of the structural transformation during hydrogenation at a fixed temperature was measured by in situ XRD. The two-dimensional plot of the XRD intensity as a function of the angle of incidence in Figure 2a shows the evolution of the structural transformation during hydrogenation at 300 °C.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…22 The orbital and spin states in manganites are easily tunable by symmetry breaking or lattice distortion driven by strain 23 and the emergence of cooperative charge and orbital ordering phenomena are found to correlate with structural transformations resulting in order−disorder transitions from changes in charge, spin, orbital, and lattice DOFs. 9,17,23,24 The poor understanding of the fundamental mechanisms of hydrogenation and the lack of systematic studies of the hydrogenation process are related to the difficult detection of hydrogen, or protons, primarily because of their size and lightweight. 7 The first step toward understanding the atomic mechanisms of hydrogen-induced transformations is the quantification of the amount and the distribution of hydrogen throughout the lattice.…”
Section: ■ Introductionmentioning
confidence: 99%